Penggambaran Budaya Jawa dalam Weird Genius ‘Lathi’ - Rafi Rizkiano; Dyah Kusumawati (UNIVERSITAS KALBIS, 2022)
Culture is a social reality that is packaged by the mass media. Javanese culture becomes a concept and theme in Weird Genius' Video Clip 'Lathi'. This study aims to determine the depiction of Javanese culture that appears in the Weird Genius 'Lathi' Video Clip using the constructivism paradigm. This study uses the Social Reality Construction Theory in the mass media. This research approach is qualitative with semiotic analysis of Charles Sanders Peirce. The results of this study found that the depiction of Javanese culture appears in the clothes and accessories used which are relevant to the values of struggle, resistance, strength, power, life, and relationships, the depiction of Javanese culture appears in the form of Gamelan art as an instrument of encouragement in resistance, Wayang as a transition between scenes as well as symbols of characters in the story, and Kuda Lumping which symbolizes war, struggle, and suffering, depictions of Javanese culture also appear in the form of language from a Javanese proverb that describes a karma, for evil deeds committed by every human being.